Preparedness of Emergency Room Nurses After Emerging Infectious Diseases Screening - Laksmi, Ida Ayu Agung; Susila, I Made Dwie Pradnya; Suprapta, Made Ani (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Emerging infectious diseases (EID) is one of the leading causes of death worldwide since it initially attacks a population or has existed before but is increasing very rapidly in terms of the number of new cases in a population. Early detection of EID patients refers to early screening. Screening of patients with suspected EID such as Covid-19 or other airborne infectious diseases must be performed at the first contact with suspected patients. This study aims to evaluate the effectiveness of EID screening instrument applied at the Emergency Room (ER). This was a quantitative pre-experimental study with a one-group pretest-posttest design. The sample size consisted of 34 nurses at the ER of Mangusada Hospital, Bali, who were selected using a total sampling technique. The intervention administered in this study was the implementation of EID screening instrument before the patients entered triage for 1 month on June 2022 at the ER of Mangusada Hospital. After ensuring the distribution and homogeneity of the data, a paired t-test was employed for parametric statistical data analysis. The result of the study showed a p-value of (0.004) or p <α (0.05). So, it can be concluded that there was an effect of the screening instrument applied at the ER of Mangusada Hospital on the preparedness of nurses in dealing with EID. Thus, the screening for patients with EID should be implemented in each emergency unit. The study finding can help improve nurse preparedness regarding the prevention of EID. In addition, future study is recommended to assess the competence of nurses regarding the prevention of EID.